PEMBERDAYAAN REMAJA DESA PESANGGRAHAN DALAM MENGEMBANGKAN BISNIS FASHION MELALUI MEDIA SOSIAL DAN PENGOLAHAN INFORMASI - Ahmad Munir Hamid (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2022)
The changing media landscape and technological advancements have had a significant impact on consumer behavior, especially among teenagers, who are increasingly engaged in the digital world. This study aims to investigate the influence of social media in shaping information processing and perceptions of adolescent consumers in Sanggrahan Village, especially on fashion products. The research method uses a qualitative approach with data collection techniques through in-depth interviews, observation, and analysis of social media content. The study participants consisted of teenagers in Pesanggrahan Village who actively used social media to get information related to fashion products. The results showed that social media acts as the main platform in providing information and designing perceptions related to fashion products among adolescents in Pesanggrahan Village. Their information processing process is driven by visual content, product reviews, and trends uploaded online. In addition, social media also plays an important role in shaping brand image and fashion product preferences.